The Vatican Apostolic Library and philanthropy - Luigina Orlandi; Mauro Mantovani (Conservation Science in Cultural Heritage)
This article, accompanied by more than 30 images, presents certain philanthropic experiences that have been in place at the Vatican Library since the 1920s. The Library has always been at the service of studying thanks to the generosity and support of the Holy See, which over the centuries has collected and guarded a wealth of documents of great value and interest. In order to carry out some major projects aimed at improving the spaces of the building it has occupied since the end of the 16th century, and the services it offers, the Vatican Library has welcomed the generous support of organizations, companies and individual benefactors. These have made it possible and continue to make it possible to carry out the renovations and reorganization of the available spaces, and to conserve the treasures entrusted to it in the best possible way, while at the same time making them increasingly accessible through technological tools, not only to the public of specialists, but to everyone. For this reason, we express our deepest gratitude to each and every one of them.